2013
DOI: 10.1002/ijc.28584
|View full text |Cite
|
Sign up to set email alerts
|

Development of serum parameters panels for the early detection of pancreatic cancer

Abstract: Early detection of pancreatic cancer is promising for improving clinical outcome; however, no effective biomarker has yet been identified. Here, we detected 61 clinical serum parameters in 200 healthy controls (Ctrls), 163 pancreatic ductal adenocarcinoma (PDAC) patients and 109 benign pancreatitis patients (Benign) in the training group. A metropolis algorithm with Monte Carlo simulation was used for identifying parameter panels. Sera from 183 Ctrl, 129 PDAC and 95 Benign individuals were used for cross-valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 45 publications
1
39
1
2
Order By: Relevance
“…In the present study, we found that levels of the serum marker of acute inflammation (CRP) and an inflammatory mediator (TNFSF13) were significantly higher in patients with PDAC-DM than in those without diabetes and in pancreatitis patients. Though the serum levels of CRP and TNFSF13 in patients with PDAC-DM were not directly compared with those of healthy individuals in our study, the serum CRP and TNFSF13 levels in patients with chronic pancreatitis were shown to be slightly higher and the same as those of healthy individuals, respectively [18][19][20]. Our data demonstrated similar levels of CRP mRNA expression in tissues from patients with and without PDAC-DM, and in patients with chronic pancreatitis, excluding the possibility that PDAC lesions are the source of the elevated CRP in the serum of patients with PDAC-DM.…”
Section: Discussioncontrasting
confidence: 66%
“…In the present study, we found that levels of the serum marker of acute inflammation (CRP) and an inflammatory mediator (TNFSF13) were significantly higher in patients with PDAC-DM than in those without diabetes and in pancreatitis patients. Though the serum levels of CRP and TNFSF13 in patients with PDAC-DM were not directly compared with those of healthy individuals in our study, the serum CRP and TNFSF13 levels in patients with chronic pancreatitis were shown to be slightly higher and the same as those of healthy individuals, respectively [18][19][20]. Our data demonstrated similar levels of CRP mRNA expression in tissues from patients with and without PDAC-DM, and in patients with chronic pancreatitis, excluding the possibility that PDAC lesions are the source of the elevated CRP in the serum of patients with PDAC-DM.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, many of experimental studies have characterized that there was higher serum level of IL-8 in patients with PDAC compared to healthy controls, suggesting the diagnostic potential as novel clinical marker of PDAC patients. 40,41 In conclusion, the present study represented a reciprocal relationship between PDAC cells and tumor-driven like macrophages. As a multifunction chemokine, IL-8 in our study was just investigated its effect on EMT switch in PDAC cells, and hence further exploration will certainly be necessary to figure out its other effect on cancer stem cell, angiogenesis, and chemoresistance.…”
Section: Discussionsupporting
confidence: 54%
“…Some of the proteins, such as IL10, ID1 and IL2, had been implicated as possible biomarkers of pancreatic cancer before [4143]. However, the result sheds new light on the process by which marker molecules should be selected for a useful diagnostic signature.…”
Section: Discussionmentioning
confidence: 99%